Surgical-first approach in skeletal class III malocclusion - a case report - Cheong, Joo Ming; Abu Bakar, Noraini; Subramaniam, Pram Kumar; Ismail, Izzati Nabilah Ismail; Nasir, Siti Hajjar; Mohd Ali, Azrul Safuan; Ahmad Basri, Nadzirah (2019)
The prevalence of Class III malocclusion is greater in Asian populations, with an estimated 17% reported in Malaysian population. Traditionally, orthodontics-first approach, which involves comprehensive orthodontic treatment to align the dental arch and incisor decompensation, followed by orthognathic surgery has been the mainstay of skeletal Class III management. However, this is a lengthy process which potentially wears out patient’s compliance. The surgery-first approach in orthognathic surgery for the early correction of skeletal, soft tissues and dental problems has recently created an interest among clinicians in eliminating time-consuming pre-operative orthodontic treatment. This case report illustrates our university’s premier surgery-first approach in the management of severe jaw disproportion.